STUDY OF THE POSSIBILITY OF USING CATGUT AS A CARRIER SUBSTANCE FOR ANTISEPTICS TO PREVENT RECOLONIZATION OF PATHOGENIC BACTERIA - Ivanytskyi, I.O.; Petrushanko, T.O.; Ivanytska, O.S.; Lokes, K.P.; Moshel, T.M. (World of Medicine and Biology, 2025)
To achieve high efficiency in the treatment of patients with chronic generalized periodontitis, in recent years, therapeutic agents immobilized on natural or synthetic polymers, which are placed directly in the periodontal pocket, have been used. In this regard, the possibility of using catgut as a carrier substance for antiseptics to prevent recolonization of pathogenic bacteria was assessed. The studies were conducted on standard cultures of Staphylococus aureus, Streptococcus gallolyticus, Streptococcus agalactiae and Porphyromonas gingivalis. It was found that catgut has the ability to be saturated with antiseptic solutions, as evidenced by the long-term antibacterial effect of chlorhexidine and decasan on periodontal microorganisms. This allows us to significantly expand the scope of application of catgut as a stable complex for the transport of antiseptic substances.